Signifikansi Pendidikan Kristen di Ruang Publik: Sarana Penggembalaan dalam Pembentukan Diri dan Dampak Sosialnya - Gultom, Yohansen Wyckliffe (JURNAL DIAKONIA, 2025)
This research concludes that Christian education has an important role in the public sphere. As a continuation of Christ's work to make disciples, schools, churches, and families also play a role in continuing the task of Christian education as partners with God. Each party certainly serves according to its respective callings, and as partners of God. The role of Christian education in public spaces includes shepherding students in forming Christian spirituality in society, encouraging the creation of social action, contributing to integrating God's word into society, and encouraging them to be actively involved in civil government or contributing to the country's development agenda. The theological thoughts used in this article include Abraham Kuyper, John Calvin, Martin Luther, Thomas à Kempis, John Owen, and a number of theologians in this century. This research is a type of qualitative research using the literature study method.